Nitrogen fixation in trees and soil fertility - Franco, Avílio A. (Pesquisa Agropecuaria Brasileira, 2014)
Second to nitrogen, phosphorus deficiency is the most wide spread limiting factor, present in about 80% of tropical soils. Erosion may affect 75% of the land area of the tropics, and salinity and alkalinity 7%. Acidity and related factors (Al and Mn toxicity and Ca and Mo deficiency) may affect 30% of these soils while other deficiencies as S, K and Zn are present in 5 to 10% of these soils, comprising mostly high rainfall areas. Nitrogen fixing trees may constitute the most desirable system for high protein yield, water and nutrient efficiency and protection against erosion. They can add large amounts of nitrogen to the soil-plant system (above 500 kg/ha/year) and at the same time return to the upper horizon nitrate, K, Ca and Mg from the lower profiles. The acidity generated in the rhizosphere of N2 -fixing plants may increase phosphate uptake from low solubitility rock-phosphate and the high P content of decomposing legume tissue may also be a good source of this nutrient for intercrops or succeeding crops. The acidity generated by N2 -fixing plants on the long run may lower soil pH specially in soils with low buffering capacity and periodic liming may be necessary to maintain high productivity. However, the higher organic matter content of soils under N2 -fixing trees may allow high yields at lower levels of pH than usually recommended  in conventional cropping systems.
Keywords: tropical soils; water use; nutrient use; rhizosphere; acidity; buffering capacity